Redox Modulating NRF2: A Potential Mediator of Cancer Stem Cell Resistance. (22nd November 2015) - Ryoo, In-geun; Lee, Sang-hwan; Kwak, Mi-Kyoung
Abstract : Tumors contain a distinct small subpopulation of cells that possess stem cell-like characteristics. These cells have been called cancer stem cells (CSCs) and are thought to be responsible for anticancer drug resistance and tumor relapse after therapy. Emerging evidence indicates that CSCs share many properties, such as self-renewal and quiescence, with normal stem cells. In particular, CSCs and normal stem cells retain low levels of reactive oxygen species (ROS), which can contribute to stem cell maintenance and resistance to stressful tumor environments. Current literatures demonstrate that the activation of ataxia telangiectasia mutated (ATM) and forkhead box O3 (FoxO3) is associated with the maintenance of low ROS levels in normal stem cells such as hematopoietic stem cells. However, the importance of ROS signaling in CSC biology remains poorly understood. Recent studies demonstrate that nuclear factor-erythroid 2-related factor 2 (NRF2), a master regulator of the cellular antioxidant defense system, is involved in the maintenance of quiescence, survival, and stress resistance of CSCs. Here, we review the recent findings on the roles of NRF2 in maintenance of the redox state and multidrug resistance in CSCs, focusing on how NRF2-mediated ROS modulation influences the growth and resistance of CSCs.